THE CORRELATION BETWEEN THE INTENSITY OF YOUTUBE USAGE AND VOCABULARY ACQUISITION IN ENGLISH LANGUAGE LEARNING - Prabaningtyas, Hana Lintang; Wulandari, Mega (LP3M Universitas Islam Zainul Hasan Genggong, 2023)
Vocabulary acquisition is significant in language learning and entails sufficient language exposure. YouTube is a video sharing platform that has been proven by studies for carrying positive impacts in vocabulary learning and acquisition. This research aimed to find how intense is the students’ YouTube usage and investigate the correlation between the two variables. Therefore, it is a correlational study. The participants were 58 CLS II students from English Language Education Study Program of Sanata Dharma University. A two weeks journal and B2 CEFR vocabulary test were used as the instruments of this research. The participants were filling the journal in 14 days to record their YouTube usage intensity. Then, they were tested using B2 CEFR vocabulary test to measure their vocabulary acquisition. The data gathered were tested using Pearson’s Product Moment Simple Correlation formula. The result shows that the student’s YouTube usage intensity ranges from 85 to 629 minutes in 2 weeks and most of the students were at the moderate level. Then, there was a weak positive correlation between the intensity of YouTube usage and vocabulary acquisition, and the correlation was significant. Therefore, both teacher and English language learners could consider utilizing the application to enhance vocabulary acquisition.